Collaborative cheating among chinese college students: the effects of peer influence and Individualism-Collectivism orientations. Issue 1 (2nd January 2020) - Zhang, Yinxia; Yin, Hongbiao
Abstract: This study addressed the neglected issue of the effects of peer influence and the cultural dimensions of individualism-collectivism on collaborative cheating. Survey data were collected nationwide from 2293 Chinese college students. The results revealed positive effects of peer influence on collaborative cheating attitudes and behaviours. Contrary to the assumptions of prior studies, horizontal individualism was the dominant inclination. Horizontal and vertical collectivism were generally negatively associated with, and exerted insignificant joint effects (with peer influence) on, collaborative cheating attitudes and behaviours; while horizontal and vertical individualism had significant direct and joint effects (with peer influence) on collaborative cheating attitudes. These unexpected findings may be partially explained by the rising individualism in the changing Chinese culture, and also by the different target groups of Chinese students in the prior research and this study (i.e. abroad versus domestic). These findings call for caution against making oversimplified assumptions about the links between culture and academic dishonesty.